Informal Learning Medium Among Gen Z Undergraduate Students - Zulkifli, Khair; Sufi Syuhadah, Supian; Nor Mazlina, Ghazali; Ida Idayu, Muhamad (Penerbit UTM Press, 2025)
Many studies show the dominance of informal learning in various contexts including in higher education institutes. Informal learning, characterized by its unstructured and self-directed nature, plays a crucial role in the educational experiences, especially for Gen Z, a generation known for its technological fluency and preference for flexible learning approaches, increasingly relies on informal mediums such as social media platforms, online forums, and video-sharing sites for knowledge acquisition. These mediums not only complement formal education but also offer personalized and engaging ways to explore diverse topics. This study investigates the most commonly used informal learning mediums among Gen Z undergraduate students, the factors influencing their preferences, and the impact on their academic and personal development. Data was collected through surveys with undergraduate students who studied informal learning through Adult Learning subject at Universiti Teknologi Malaysia. Findings reveal a strong inclination towards visually interactive platforms and peer-to-peer learning environments, highlighting the need for educational institutions to recognize and integrate these mediums into broader learning frameworks. By understanding how Gen Z students leverage informal learning, this research provides insights for educators and policymakers to enhance student engagement and support lifelong learning in an increasingly digital world and also encourages the use of selective medium for informal learning.